Bimodality in zircon oxygen isotopes and implications for crustal melting on the early Earth - Kirkland, Chris; Johnson, Tim; Gillespie, Jack; Martin, L.; Rankenburg, Kai; Kaempf, Jonas; Clark, Chris (2024)
Zircons from the oldest dated felsic crust, the Acasta Gneiss Complex, Canada, provide key information that may help understand the generation of crust on our nascent planet. When screened to eliminate grains with secondary alteration by measuring relative hydration (Δ16O1H/16O), primary ≥ 3.99 Ga zircon cores show δ18O of 5.88 ± 0.15 ‰, at the extreme upper (heavy) range for mantle values. Another early (≥3.96 Ga) zircon component indicates distinctly different, primary light δ18O values (δ18O ≤ 4.5 ‰). This bimodality in ancient zircon oxygen isotopes implies partial melting of both deep (lower crustal) and shallower (near surface) source rocks, responsible for felsic crust production on the early Earth. A similar bimodality in zircon δ18O is recognised in data from other ancient cratons, albeit at different times. Although alternative (uniformitarian) interpretations may also satisfy the data, the tempo of this bimodality matches models of planetary high-energy impact flux, consistent with a fundamental role for bolide impacts in the formation of crustal nuclei on the early Earth.